The role of TDP-43 protein in amyotrophic lateral sclerosis (Journal of Medical Science, 2022)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease where both upper and lower motoneurons are damaged. Even though the pathogenesis of ALS is unclear, the TDP-43 aggregations and non-nuclear localization may be crucial to understanding this process. Despite intensive research on ALS therapies, only two lifespan-prolonging medications have been approved: Riluzole and Edaravone. Unravelling the TDP-43 pathology could help develop new ALS therapies using mechanisms such as inhibition of nuclear export, autophagy, chaperones, or antisense oligonucleotides. Selective inhibitors of nuclear export (SINEs) are drugs that block Exportin 1 (XPO1) and cause the accumulation of not exported molecules inside the nucleus. SINEs that target XPO1 are shown to slightly extend the survival of neurons and soften motor symptoms. Dysfunctional proteins, including TDP-43, can be eliminated through autophagocytosis, which is regulated by the mTOR kinase. Stimulating the elimination of protein deposits may be an effective ALS therapy. Antisense oligonucleotides (ASO) are single-stranded, synthetic oligonucleotides that can bind and modulate specific RNA: via ribonuclease H, inducing their degradation or inducing alternative splicing via blocking primary RNA transcripts. Current ASOs therapies used in ALS focus on SOD1, C9ORF72, FUS, and ATXN2, and they may be used to slow the ALS progression. Reversing the aggregation is a promising therapeutic strategy. Chaperones control other proteins’ quality and protect them against stress factors. Due to the irreversible character of ALS, it is essential to understand its complicated pathology better and to seek new therapies.